Segundo ano de avaliação da influência do porta-enxerto da série “Geneva” na ocorrência da sarna da macieira na cultivar gala - Zanrosso, Arthur (My University, 2025)
The cultivation of apple trees in Brazil is an example of success in the fruit industry, since in the last three decades the country has gone from being a small producer and is currently a reference in fruit production. Because the demand for the product is constant, there is a need for increased productivity in the producing areas. For this increase to be achieved, the use of pineapple rootstocks, enabling a greater density of plants in the orchards, is essential. Knowing that phytosanitary treatments, essential for the control of several diseases of the culture, represent the largest expenditure in the sector, we sought to analyze the influence of Geneva series rootstocks on the incidence and severity of apple scab in the Gala cultivar, as a way to maximize gains and facilitate management. The experiment was conducted in randomized blocks, with five different rootstocks of the Geneva series and CAT 16, with the coppiced cultivar Gala Select. Each plot consisted of 10 plants, of which eight central plants were considered useful and the others as border. The percentage of incidence and severity of apple scab on leaves was evaluated every two weeks, in addition to the same evaluations for harvested fruit. With the data obtained, the Area Under the Disease Progress Curve (AACPD) was calculated. The data was submitted to variance analysis and the means were compared using the Tukey test at 5% probability. The results revealed that the rootstocks used did not influence the increase in the disease of apple scab, in the cultivar Gala Select. [resumo fornecido pelo autor]
A cultivo da macieira no Brasil é um exemplo de sucesso no meio do setor frutícola, visto que nas últimas três décadas o país saiu de pequeno produtor e, atualmente, é referência em produção da fruta. Em virtude de a demanda pelo produto ser constante, há a necessidade do aumento de produtividade nas áreas produtoras. Para que esse aumento seja alcançado, a utilização de porta-enxertos ananizantes, possibilitando uma maior densidade de plantas nos pomares, é essencial. Sabendo que os tratamentos fitossanitários, essenciais para o controle de diversas doenças da cultura, representam o maior gasto do setor, buscamos analisar a influência dos porta-enxertos ananizantes da série Geneva sobre a incidência e severidade de sarna da macieira na cultivar Gala, como forma de maximizar os ganhos e facilitar o manejo. O experimento foi conduzido em blocos casualizados, com cinco diferentes porta-enxertos da série Geneva e CAT 16, com a cultivar copa Gala Select, sendo cada parcela constituída de 10 plantas, as quais foram consideradas úteis as 8 plantas centrais e as demais como bordadura. Foi avaliada a porcentagem de incidência e severidade de sarna da macieira em folhas, quinzenalmente, além das mesmas avaliações para frutos de colheita. Com os dados obtidos, calculou-se a Área Abaixo da Curva de Progresso da Doença (AACPD). Os dados foram submetidos à análise de variância e as médias comparadas pelo Teste de Tukey a 5% de probabilidade. Os resultados revelaram que os porta-enxertos utilizados não influenciaram no aumento da doença sarna da macieira, na cultivar Gala Select. [resumo fornecido pelo autor]
Keywords: Agronomia; Maça - Cultivo; Pragas agrícolas